Antenatal Diagnosis of Subependymal Heterotopia - Mitchell, L. Anne (AJNR Am J Neuroradiol, 2000)
Summary: Subependymal heterotopia consist of gray matter nodules along the lateral ventricular walls and are associated with epilepsy and other cerebral malformations. Some cases have an X-linked inheritance, and early antenatal diagnosis of affected fetuses is important for appropriate management. We present a case of heterotopia diagnosed by sonography and MR imaging at 23 weeks' gestation and discuss the differential diagnosis, reviewing the evolution and imaging appearances of the germinal matrix and its implications for detection of heterotopia.